Highly efficient coupler for dielectric slot waveguides and hybrid plasmonic waveguides. (6th April 2018) - Yu, Jiyao; Ohtera, Yasuo; Yamada, Hirohito
Abstract: A compact, highly efficient optical coupler for dielectric slot waveguides and hybrid plasmonic waveguides based on transition layers (air slot grooves) was investigated. The power-coupling efficiency of 75% for the direct coupling case increased to 90% following the insertion of an intermediate section. By performing time-averaged Poynting vector analysis, we successfully separated the factors of transmission, reflection, and radiation at the coupler interface. We found that the insertion of optimal air grooves into the coupler structure contributed to the improvement of coupling performance. The proposed compact structure is characterized by a high transmission efficiency, low reflection, small length, and broad-band spectrum response.